TEACHER BELIEFS OF ENGLISH GRAMMAR INSTRUCTION IN MERDEKA CURRICULUM - Azalia, Syafina; Triastuti, Anita; Margana, Margana (Journal of English Educational Study (JEES), 2025)
As one of the essential elements in mastering the English language, grammar teaching remains a subject of debate. While the Merdeka curriculum encourages students to be more active in class and become independent learners, some teachers prefer to teach grammar in an isolated and explicit manner, while others believe in teaching grammar implicitly and within context. Given this issue, understanding teachers' beliefs about grammar is crucial to uncovering how they teach it in the classroom. This study aims to explore the teaching practices of two teachers at a reputable high school in Yogyakarta. Employing a descriptive qualitative method, the study used observation and open-ended interviews to gather data. In analyzing the data, the study applied the framework of Graus & Coppen (2016) to specify the grammar instruction strategies used by the teachers. The findings revealed that both teachers align with the goals of the Merdeka curriculum, which aims to foster independent learning by implementing various grammar instruction methods, such as Meaning-Focused Instruction that emphasizes linguistic function rather than form, Focus on Form (FonF) technique that concentrate on correcting grammar errors through student reflection rather than direct error correction, Implicit instruction which integrates grammar learning in real-life contexts, and Inductive Teaching Strategies that encourage critical thinking by having students deduce grammar rules from examples in the text rather than being explicitly taught the rules. Therefore, this study demonstrates that both teachers' methods align with the goals of the Merdeka curriculum.